ADVERSITY QUATION IMPROVEMENT AND GEOGRAPHY LEARNING OUTCOMES THROUGH PROBLEM BASED LEARNING MODEL IN STKIP AHLUSSUNNAH BUKITTINGGI STUDENTS - Alexander Syam; Tiara Suci Ramadhani; Serli Muchlian; Zamhar Bakri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat STKIP Ahlussunnah, 2023)
Based on the learning outcomes of STKIP Ahlusunnah Bukitgi geography students, it was found that the Adversity Quation and student learning outcomes were still very low. Adversity Quation average and student learning outcomes are still below the KKM. The purpose of this study was to describe and obtain information about increasing Adversity Quation and Learning Outcomes through the Problem Based Learning learning model for STKIP Ahlussunnah Bukittinggi students. This research is a classroom action research. The research procedure in this study includes planning, action, observation and reflection. This study consisted of two cycles with four meetings. The research subjects consisted of 32 geography students at STKIP Ahlusunnah Bukittinggi. Research data was collected using observation sheets and UTS. Data were analyzed using percentages. Based on the results of the research and discussion that have been put forward, it can be concluded that the Problem Based Learning learning model can improve Adversity Quation and student learning outcomes. Adversity Quation in cycle I was 72.46 (Enough), increased in cycle II, namely 82.03 (Good) so that it experienced an increase of around 9.57%. While student learning outcomes in cycle I was 74.72 (Enough), increased to 81.83 (Good) in cycle II with an increase of 7.11%.